Large heterogeneity in body composition and performance characteristics of high-level youth hockey players - Cintineo, H.; Arent, M.; McFadden, B.; Chandler, A.; Bozzini, B.; Sanders, D.; Walker, A.; Arent, S. (The Journal of Strength and Conditioning Research, 2021)
Purpose: To assess body composition (BC) and performance characteristics of high-level youth hockey players. Methods: BC and performance metrics were assessed in 16 high-level male hockey players from different clubs (10 forwards, 4 defensemen, 2 goalkeepers; M age: 15.4 BC0.5 years). Athletes arrived for testing >2 hours fasted and having refrained from exercise for =24 hours. Body mass (BM) was measured using a calibrated scale. Body fat percentage (%BF) and fat-free mass (FFM) were determined via air-displacement plethysmography. Anaerobic power was then assessed via countermovement jump (CMJ) height using a digital contact mat. Lastly, aerobic capacity (Vo2max) and ventilatory threshold (VT) were measured via indirect calorimetry using a maximal graded-exercise test. On a separate day, the Wingate anaerobic test (WAnT) was conducted using an electronically braked cycle ergometer to measure absolute and relative peak and mean power (APP; RPP; AMP; RMP) and fatigue index (FI). All testing occurred as a part of normal team activities; informed consent was waived by the IRB. Descriptive statistics are presented as mean aSD, range, and min/max values. Correlations (r) were used to assess relationships between variables (a = 0.05). Results: Mean BM was 73.2 Me14.5 kg and ranged from 61.1 to 111.0 kg. Similarly, %BF (16.3 4.0.1%) ranged from 8.3 to 28.4%, and FFM (60.5 .17.8 kg) ranged from 45.9 to 65.5 kg. Further, mean CMJ height was 58.3 .87.2 cm with a range of 23.4 cm. Mean APP was 1,250 50316 W with a range of 1017 W, while mean RPP was 17.3 161.0 W/kg. Mean AMP was 729 .0124 W (range: 581-986 W), and mean RMP was 10.2 860.9 W/kg. Additionally, mean FI was 25.9 .90.1% (range: 14-44%). Mean Vo2max was 57.8 wa5.8 ml/kg/min and ranged from 45.9 to 65.5 ml/kg/min with VT at 74.9 kg0.4%Vo2max. BM was strongly correlated with APP (r = 0.98, p< 0.001), AMP (r = 0.91, p< 0.001), and FI (r = 0.90, p< 0.001). APP and FI were also strongly correlated (r = 0.95, p< 0.01). WAnT variables were not correlated to CMJ (r < 0.4, p > 0.05) or Vo2max (r < 0.6, p > 0.05). Conclusions: There was substantial heterogeneity in BC and performance variables in this sample of high-level youth athletes. There are limited data in high-level youth hockey players, though research in collegiate and professional counterparts has shown lower %BF than those seen in these athletes. This difference is likely attributed to differences in age and competition levels. Despite large variances in CMJ height, APP, AMP, FI, and Vo2max, RPP and RMP values were less variable which indicates a standard level of anaerobic power relative to BM is required in these athletes. This analysis also shows that there is a trade-off between peak power output and anaerobic capacity in these athletes, though more research is needed to determine which is a more favorable characteristic. The observed correlations show that those with the highest BM produced the highest power but also have the lowest anaerobic capacities. Lastly, the weak relationship between CMJ and WAnT, which requires movement patterns similar to skating, shows this test may be more appropriate in hockey players. Practical Applications: Large variances in BC and performance metrics in this sample suggest that no single laboratory-measured performance profile can be used to determine athlete recruitment into high-level hockey clubs. This study also supports the notion that sport movement-specific tests are most appropriate when assessing performance in various athletes.